Serum Adipokines as Predictors for the Outcome of Prostate Biopsies at Early Stage Prostate Cancer Diagnosis - Ahmad, Ardalan E. (2019)
Purpose: Elevated adipokines in patients with obesity and metabolic syndrome have been linked to increased risk of prostate cancer (PCa). The association between select serum adipokines and the outcome of prostate biopsies alone and in combination with clinical parameters at different early stages of PCa was investigated. Patients and methods: Clinical data and serum adipokines were retrieved from three retrospective cohorts representing men at different points in PCa detection: 1. Subjects with no prior biopsies (n=1061), 2. subjects with a prior negative biopsy (REDUCE trial, control arm) (n=1209), 3. subjects with low-risk PCa on active surveillance (AS) (n=154). Adipokines were chosen based on an unpublished pilot study and included: Resistin, Tumor Necrosis Factor-α, Interleukin-6, Monocyte Chemoattractant Protein-1, Hepatocyte Growth Factor, and Nerve Growth Factor. The primary outcome was the absence of PCa on biopsy and the secondary outcome was diagnosis of low-risk PCa fitting the criteria for continuing AS. Logistic regression analysis was used to assess the association of adipokines and negative and/or low-risk PCa at prostate biopsy. Results: In men with no prior prostate biopsy or with prior negative biopsy, adipokines were not predictors of prostate biopsy outcomes on multivariable regression analysis controlling for known clinical variables. In the AS cohort, MCP-1 and Resistin were significant predictors of biopsy outcome on multivariable analysis (OR 0.20, 95% CI: 0.05–0.85, p= 0.03 & OR 0.30, 95% CI: 0.10 −0.86, p= 0.03). Conclusion: Our findings do not support a strong role for adipokines for predicting the outcome of prostate biopsies at any early stage in PCa diagnosis.